Membumikan Laporan Keuangan untuk Penghafal Al-Quran - Puji Wibowo; Ahmad Khizazi; Azaz Mabrur (Journal of Dedicators Community, 2019)
Alquran-based educational institutions are one of the most important supplier of the nation's generation of noble character, love of the motherland, and global outlook. The survival of these educational institutions is determined, among other things, by the organization's sound and transparent financial management. Financial reports are an instrument for educational institutions to evaluate performance and plan activities that are realistic and adaptive to change. Islamic Education Foundation Islamic Boarding School Alquraniyah (YPI-PPA) East Jurangmangu, Pondok Aren, South Tangerang has the responsibility to give birth to the nation's cadres who are polite, love the Koran, and ready to contribute to the wider community. Fostering financial management, especially in preparing financial statements, is crucial for stakeholders who need a guarantee of business continuity from the educational institution. The synergy between students and lecturers at the State Financial Polytechnic STAN has sought to raise awareness for YPI-PPA employees to begin cleaning up in preparing financial reports that are more comprehensive, accountable, and provide full information for decision makers.